ASEAN, INDONESIA DAN RUSIA TIMUR JAUH: PELUANG DAN DIVERSIFIKASI [ASEAN, INDONESIA AND RUSSIA FAR EAST: OPPORTUNITIES AND DIVERSIFICATION] - Adri Arlan (Universitas Pelita Harapan, 2019)
Indonesia-Russia relations started at the end of World War II. Early relations were poor but became close during the Sukarno period. The post-Soviet era ushered a new height of Russia’s political, diplomatic, and economic presence in Southeast Asia. After the dissolution of the United Soviet Socialist Republic (USSR), Russia has focused on a grand re-engineering project, an important component of institutional stability. Part of the re-structuring included ambitious actions to re-brand a powerful image of her position in Southeast Asia, and in Asia and the Pacific, in general. Scholars have argued that there is a lack of knowledge in terms of Russia’s relations with countries of Southeast Asia (ASEAN). This can be explained by Russia’s unfamiliarity over the region’s diversity and by her insecurity with the dominance of the United States and China, among others. Nevertheless, the Putin Government has shifted its lens towards the Southeast Asian region by establishing stronger ties in areas of security and defense, energy development, and trade and people-to-people exchanges. This paper employs an ‘ethic’ perspective analysis of the actions taken by Russia in these areas and suggests possible future actions to enhance collaboration and cooperation with Southeast Asian countries such as Indonesia.BAHASA INDONESIA ABSTRAK: Hubungan Indonesia-Rusia telah dimulai sejak berakhirnya Perang Dunia ke II. Kerja sama yang terjadi antara kedua negara terjalin cukup erat di era Presiden Sukarno. Pasca runtuhnya Uni Soviet terjadi perubahan dinamika dalam hubungan politik, diplomatik dan ekonomi Rusia di Asia Tenggara. Saat ini Rusia fokus dalam menata ulang grand strategy penguatan kestabilan institusi baik dalam maupun luar negeri. Dalam hal penataan ulang kebijakan strategi luar negeri, Rusia berupaya untuk menciptakan image baru di Asia Tenggara dan Pasifik. Secara umum, para ahli berargumen bahwa masih minimnya wawasan dalam konteks hubungan Rusia dan Asosiasi Negara di Asia Tenggara (ASEAN). Hal ini dijelaskan dengan minimnya peran Rusia dalam hal kerja sama dan insekuritas akibat dominasi Amerika Serikat dan Republik Rakyat Tiongkok yang sudah mengakar kuat di kawasan. Namun demikian, administrasi Putin mencoba meningkatkan perhatiannya ke ASEAN dengan meningkatkan ikatan kerja sama dalam sektor pertahanan dan keamanan, energi, perdagangan dan people to people contact. Tulisan ini mengulas pendekatan ‘etis[’ berupa pola kebijakan kerja sama yang diimplementasikan oleh Moskow serta rekomendasi diversifikasi kerja sama Rusia dengan negara di Asia Tenggara seperti Indonesia.